The effectiveness of HOTS English module in English teaching and learning - Hikmah, Harisna; Wibowo, Edy Wahyu (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2020)
Today's curriculum is focused on Higher Order Thinking Skills to improve the quality of learning and the graduates. So that, today the teaching and learning materials and activities for the students are recommended to be implemented. This study is aimed to know the effectiveness of HOTS English module in the English teaching and learning process in MTs Al Falaah Pandak. This is a quasi-experimental study which is implemented pre-test and post-test group design. To collect the data, the researcher used test as the instrument. The data then analyzed used t-test. The result of the study shows that HOTS English module is effective in improving the seventh-grade students' achievement in learning English in MTs Al Falaah Pandak. The result of two tailed t-test from the data analysis is 0.000. It is smaller than 0.05 which means that Ho is denied. So, it can be concluded that there is significance of the students' achievement before and after applying HOTS English module in learning English.